Numerical and Experimental Analysis of Radial Compression in Umbilical Cables Using the Finite Alement Method - Bruno da Cunha Diniz; Maria Vitória dos Santos Alcântara e Figueiredo; Rui Felipe Cardoso Queiroz; Sarah Beatriz Ferreira Ramos de Cerqueira (JOURNAL OF BIOENGINEERING, TECHNOLOGIES AND HEALTH, 2026)
This study evaluates the performance of a two-dimensional numerical radial compression model applied to umbilical cables, comparing its results with experimental data. These cables are multifunctional structures essential to the oil and gas industry, responsible for interconnecting platforms and subsea systems, enabling control, monitoring, and fluid injection. Their internal configuration may include hydraulic hoses, electrical cables, optical fibers, steel tubes, filler elements, and armor layers. Installation is carried out by Pipe Laying Support Vessels (PLSVs), operating in vertical or horizontal lay modes. During installation, tensioners apply radial compression and axial tension, and, secondarily, cause radial crushing of the armor layers onto the core due to their helical arrangement. The numerical model was developed using the Finite Element Method in HyperWorks, with OptiStruct as the solver, adopting two-dimensional elements under the plane stress assumption. Loading was divided into three stages, simulating internal pressurization, shoe compression, and crushing pressure from axial tension. Layer interactions were assessed with Helica software. The results showed good agreement for residual and compressed diameters, with absolute errors <1.5 mm and relative errors <1% in most measurements. However, larger discrepancies were observed in residual ovalization, particularly for low-magnitude values, where the relative error was amplified. Thus, the use of absolute error is recommended as the criterion for evaluating sensitive quantities, such as ovalization and deformation.